Hierarchical porous NiCo2O4 nanowires for high-rate supercapacitors - Jiang, Hao (2013)
We demonstrate a simple and scalable strategy for synthesizing hierarchical porous NiCo2O4 nanowires which exhibit a high specific capacitance of 743 F g−1 at 1 A g−1 with excellent rate performance (78.6% capacity retention at 40 A g−1) and cycling stability (only 6.2% loss after 3000 cycles).